2007
DOI: 10.1159/000101727
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Cinacalcet and Paricalcitol Titration Protocol for Treatment of Secondary Hyperparathyroidism

Abstract: Long-term outcomes of combined cinacalcet and paricalcitol therapy for secondary hyperparathyroidism (SHPT) in patients failing traditional therapies with phosphate binders and active vitamin D compound analogs are not well described. We implemented a titration protocol for cinacalcet and paricalcitol and assessed its long-term effects on bone metabolism and disease in hemodialysis (HD) patients. Thirty-five patients were started on 30 mg of cinacalcet daily. After 12 months, median cinacalcet dose was 60 mg. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…For instance, Moe et al [20] in their study indicate an iPTH of 590 8 39 pg/ml with a drop to 451 8 65 pg/ml after 100 weeks of treatment with no change in s-Ca (2.42 mmol/l) and a drop in s-P from 1.87 to 1.84 mmol/l. In another study, the start iPTH of 426 8 274 dropped to 300 8 228 pg/ml, s-Ca reached the values of 2.37 and 2.20 mmol/l, respectively, and s-P 2.00 and 1.78 mmol/l, respectively [21] . In the recently published ECHO study, the mean iPTH was 721 pg/ml [18] , and in the DaVita population, it reached 576.9 8 505.8 pmol/l [17] .…”
Section: Clinical and Laboratory Impact Of Treatmentmentioning
confidence: 87%
“…For instance, Moe et al [20] in their study indicate an iPTH of 590 8 39 pg/ml with a drop to 451 8 65 pg/ml after 100 weeks of treatment with no change in s-Ca (2.42 mmol/l) and a drop in s-P from 1.87 to 1.84 mmol/l. In another study, the start iPTH of 426 8 274 dropped to 300 8 228 pg/ml, s-Ca reached the values of 2.37 and 2.20 mmol/l, respectively, and s-P 2.00 and 1.78 mmol/l, respectively [21] . In the recently published ECHO study, the mean iPTH was 721 pg/ml [18] , and in the DaVita population, it reached 576.9 8 505.8 pmol/l [17] .…”
Section: Clinical and Laboratory Impact Of Treatmentmentioning
confidence: 87%
“…Cinacalcet hydrochloride is a potent and selective type II calcimimetic agent, clinically used in primary HPT (111), secondary HPT (112)(113)(114)(115)(116)(117)(118)(119)(120)(121) and even in a case of pregnancy with hereditary hypophosphatemic vitamin D resistant rickets (122).…”
Section: A) Control Of Biochemical Abnormalitiesmentioning
confidence: 99%
“…Cinacalcet in severe secondary hyperparathyroidism a) Control of biochemical abnormalities A large number of randomized controlled trials investigated the effects of calcimimetics on the control of sHPT in patients with ESRD (112)(113)(114)(115)(116)(117)(118)(119)(120)(121). Several studies compared cinacalcet plus existing therapies -including continued, but restricted, vitamin D analog use -with standard-of-care, consisting of unrestricted use of phosphate binders and vitamin D analogs.…”
Section: A) Control Of Biochemical Abnormalitiesmentioning
confidence: 99%
“…In each study, roughly 7% of patients receiving cinacalcet experienced frank hypocalcemia, versus £1% of the calcitriol analogue-alone-treated patients. Other studies have shown comparable rates of hypocalcemia (43)(44)(45). Thus, use of cinacalcet is likely to confer risks not associated with the use of calcitriol analogues.…”
Section: Classical Effects Of Calcitriol Analogues and Calcimimetics mentioning
confidence: 95%
“…In broadly comparable fashion, the OPTIMA study demonstrated a mean PTH increase of 2% for calcitriol analogue‐alone‐treated patients, while patients on cinacalcet treatment plus low doses of calcitriol analogues exhibited a 46% reduction in PTH levels (41). Several “real‐world” studies subsequently demonstrated that cinacalcet can be used to augment calcitriol analogues to achieve superior PTH control (43,44) and to reduce use of calcitriol analogues (45), although this is not the invariable result (46).…”
Section: Efficacy Of Calcitriol Analogue and Calcimimetic Therapy Formentioning
confidence: 99%